2019
DOI: 10.1111/jocd.13021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different concentrations of hydrogen peroxide solution (3% and 6%) as a potential new therapeutic option of nongenital warts: A randomized controlled triple‐blinded clinical trial

Abstract: Warts are common skin infections with both physical and psychological impacts. 1 It is caused by human papillomavirus (HPV). HPV is an icosahedral nonenveloped, double-stranded DNA virus which can cause a variety of skin presentations according to its type, site, and the immune status. Nongenital warts may be presented as common, plane, planter, filiform, or mucosal warts. The prevalence of skin warts is between 2.4% and 12.9%. 2 Researchers are still trying to find an ideal treatment modality for warts which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 4 publications
2
16
0
Order By: Relevance
“…Non‐genital warts can be introduced as common, planter, plane, filiform, or mucosal warts. The skin warts prevalence is ranged from 2.4% to 12.9% 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non‐genital warts can be introduced as common, planter, plane, filiform, or mucosal warts. The skin warts prevalence is ranged from 2.4% to 12.9% 7 …”
Section: Discussionmentioning
confidence: 99%
“…Mahran et al 7 showed that after 6 weeks of treatment completion, 46.6% of cases in group 1 had complete response and 53.4% had partial response and no cases had no response. In group 2, 48.3% had complete response, 10.3% had partial response, and 41.4% had no response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low hydrogen peroxide concentrations cause transient symptoms such as erythema, burning, hypopigmentation, blanching, paraesthesia and blistering. 16,17,34 High concentrations are known to result in concentration and lengthdependent effects which in addition include vesiculation, erosion, crusting, hypopigmentation, hyperpigmentation and scarring. 2,31 High concentrations used to bleach hair can cause chemical burns.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…A variety of physical and chemical treatment options for the various presentations of HPVare available. An RCT found that 6% topical hydrogen peroxide served as an effective and safe treatment for non-genital warts compared to 3% hydrogen peroxide or placebo [83]. A 2017 pilot study showed clearance of 75.9% of cutaneous warts with microwave therapy, compared to 23-33% report clearance rate with cryotherapy or sialic acid, indicating microwaves may be a promising treatment for cutaneous warts [84].…”
Section: Papillomaviridaementioning
confidence: 99%